A fibrous crops harvesting system. - Ahmad, Desa (2010)

(untitled)
Kenaf is a warm season annual thick stem fibrous crop which contains two basic components: bast fibers in the outer bark and inner core of short xylem fibers. Most of the existing modified harvesters change the stem to small fragments. In addition, kenaf industries need kenaf fibers to be as long as possible. The gathering system and cutting system are designed and fabricated for a kenaf harvester attached as off-set equipment to the ordinary tractor. The V-shaped sidewalls of the present invention head help to receive, push and guide the stems to better cutting. The gathering system can keep the stems upright before and after cutting and convey the cut stems upright via a straight tunnel to off-load the stems behind the tractor. Impact rotating cutting system comprising of a large diameter disk and some special blades can cut four rows of stem, concurrently.